FeCo1.6Mn0.4O4 microspheres as catalysts for oxygen reduction reaction. Issue 2 (May 2019) - Wang, Bowen; Zhang, Ru; Lei, Ming
Abstract: The representative spinel-type materials AB2 O4 (Both of A and B are transition metals) electrocatalysts for oxygen reduction reaction (ORR) have been investigated widely. But FeCo2 O4 was not explored widely as the ORR electrocatalyst. The element of B site in AB2 O4 had a determined influence on the electrochemical performance of the sample according to the previous research. In this work, a part of Co element at B site in FeCo2 O4 was doped by Mn to improve the electrochemical performance for the popular research. FeCo1.6 Mn0.4 O4 microspheres were prepared and characterized with XRD, SEM, XPS. The electrochemical performances were tested and the results were analyzed. Meanwhile, the stability and methanol tolerance ability of catalysts were also measured. The work found a superior performance and non-precious catalyst for oxygen reduction reaction.